PENGARUH DUKUNGAN SOSIAL TERHADAP RESILIENSI AKADEMIK PADA MAHASISWA YANG MENEMPUH SKRIPSI - Afra Ulfatihah Nur Erwanto; Istiqomah Istiqomah; Retno Firdiyanti (Program Studi S1 Psikologi, 2022)
Final semester college students who are working on thesis are vulnerable to stress due to various demands and constraints during the thesis process that requires a long enough period of time, so it is important for final semester college students to have adequate resilience in order to be able overcome various difficulties and complete thesis well. One of the protective factors that can help individuals to bouncing back from all academic difficulties is social support. The purpose of this study is to determine how the effect of social support on academic resilience in college students who are taking thesis. This study uses a quantitative approach with the sampling technique used is accidental sampling. Respondents of this study amounted 198 with criteria including active college students who are working on thesis for at least one semester or six months and study in Malang. The instrument used to measure social support is MOS-SSS and the instrument used to measure academic resilience is ARS-30. The data collected were analyzed using simple linear regression and generated sig. value (p) < 0,001. These results show that there is an influence of social support on academic resilience in college students who are taking thesis. Key word: family support, peer support, external motivation